2015
DOI: 10.1007/s00520-015-2914-3
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions among cancer survivors

Abstract: Understanding how cancer survivors make sense of cancer can clarify an important aspect of adaptation. This in turn can inform interventions to facilitate adjustment. Knowledge contributions include evidence of physical symptom distress correlating with most dimensions of illness perception. Optimism was also associated with cancer survivors' illness perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 38 publications
1
35
0
7
Order By: Relevance
“…35 Increasingly patients with head and neck cancer will become long-term survivors. Consistent with previous studies, 21,36 illness perception dimensions were intercorrelated. Patients reporting more symptoms also perceived their condition to be more serious, reported greater illness concern and emotional impact and poorer understanding of illness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…35 Increasingly patients with head and neck cancer will become long-term survivors. Consistent with previous studies, 21,36 illness perception dimensions were intercorrelated. Patients reporting more symptoms also perceived their condition to be more serious, reported greater illness concern and emotional impact and poorer understanding of illness.…”
Section: Discussionsupporting
confidence: 91%
“…19 In 109 patients with idiopathic Parkinson's disease, although positive illness perceptions were associated with better wellbeing, optimism was a significant moderator of that relationship. 20 In studies of cancer, more optimistic patients tend to report less negative illness perceptions 14,21 and lower anxiety and depression as well. [22][23][24] Being mostly crosssectional, confounding and reverse causality cannot be excluded in some of the preceding studies.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 In addition, we found that higher cancer stage and more comorbidities were associated with having pessimistic IPs. Consistent with literature regarding threatening IPs, pessimistic IPs were found to be associated with sociodemographic factors, including younger age, being female, and having a low educational level.…”
Section: Discussionmentioning
confidence: 80%
“…Construct validity was assessed by correlating B-IPQ scores with physical symptom distress (MSAS-PHYS) and psychological distress (HADS-Anxiety and HADS-Depression) scores. We hypothesized that the B-IPQ would correlate with greater physical symptom distress and psychological distress [27]. All correlation was performed by Pearson’s correlation analysis.…”
Section: Methodsmentioning
confidence: 99%